A Case Report on Challenging Deep Vein Thrombosis: Life Sciences-Obstetrics and gynaecology - B.M, Dr.Logeswari; Shahi, Dr.Vatsala (International Journal of Life Science and Pharma Research, 2023)
In pregnancy, venous thromboembolism (VTE) remains a leading cause of direct maternal mortality. It is approximatelyfive times more common in pregnant women, with an incidence of 0.5-2 in 1000. The highest risk of deep venous thrombosis(DVT) leading to pulmonary embolism (PE) is during the postnatal period, especially after a cesarean section. A clinician who doesnot treat pregnant women regularly may not routinely identify pregnancy-specific risk factors for VTE. In patients with DVT,treatment with anticoagulation is associated with a high risk of bleeding during the immediate postpartum state, and patients dowell with monitored anticoagulation and proper supportive treatment, as described in this case report. We are reporting a caseof a 20-year-old primigravida who presented with labor pains at 39 (+6) weeks of gestation at Sree Balaji Medical College andHospital, Chrompet, Chennai. The patient had no comorbidities and did not report any past or family history of VTE. An emergencycesarean section was performed due to fetal distress, and on the first postoperative day, she developed swelling pain andtenderness in the left lower limb. Color Doppler ultrasound showed left anterior tibial vein thrombosis, following whichanticoagulant therapy was started with low molecular weight heparin. The patient was closely monitored for signs of bleeding orPE and was eventually discharged on oral anticoagulation. In conclusion, all women should be assessed for the risk factors of DVTduring the antenatal period, and early ambulation in the postoperative period is crucial to prevent such deadly complications.